Pengendalian Kualitas Untuk Mengurangi Botol Bocor Pada Departemen Blow Molding Di Industri Packaging - Nadia Rizki Ariyani; Renanda Nia; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
As time goes by, quality becomes one of the most important things. Indicator goodproducts, resulting from the good quality control. The product result from packaging industry variesso as to cause analysis and control processes quality becomes unequal and not maximal. In this case,the reseacher using the Six Sigma method with DMAIC’s phase (De ine, Measure, Analyze, Improve,Control). There are many tools that the reseacher used, like project charter, SIPOC’s diagram, Voiceof customer (VOC), control chart, Fault Tree Analysis (FTA), Failure Mode Effect Analysis (FMEA).From the results project charter is obtained that is the problem regarding how to reduce customercomplaints against BT products 8251 (42%) to (15%). Then the results of the control chart (u-chart)that reject of the product sent to customer has not been controlled. After that, the causes wereanalyzed using Fault Tree Analysis (FTA). Improvements are recommended to reduce defects basedon RPN (Risk Priority Number) from Failure Mode Effect Analysis (FMEA). There are severalsuggestions that are tried to be applied in the industry but it still cannot be seen being followed up.